Readiness of women 36-55 years old for self-control of motor activity - L.N. Voloshina,; S.S. Gulyaeva,; V.L. Kondakov,; E.N. Kopeikina, (Theory and Practice of Physical Culture, 2023)
Abstract Objective of the study was to identify the readiness of women aged 36-55 who plan to engage in physical culture and recreational activities, to use modern digital technologies for controlling physical activity. Methods and structure of the study. The survey involved 122 women of mature age (second period). For the study, two groups were formed for recreational fitness: 1e (n=60) of women living in a rural municipality (Churapchinsky district) of the Republic of Sakha (Yakutia), and 2e (n=62) of women living in the urban-type settlement Prokhorovka (Belgorod region). Results and conclusions. The results of the study indicate the relevance of such tasks as ensuring the availability of digital technologies, digital infrastructure, and the need to improve the computer competence of women of mature age involved in sports and recreation activities in order to minimize the risks associated with the dosage of physical activity.